Physical performance indicators and team success in the German soccer league - Chmura, P.; Oliva-Lozano, J. M.; Muyor, J. M.; Andrzejewski, M.; Chmura, J.; Czarniecki, S.; Kowalczuk, E.; Rokita, A.; Konefal, M. (Journal of Human Kinetics, 2022)
The aims of this study were (1) to determine the match running performance required by different teams based on their final ranking position and (2) to analyze the association between match running performance variables and team success at the end of the season. A total of 1,224 match observations from professional soccer teams competing during two consecutive seasons in the German Bundesliga were analyzed. In addition, the final league ranking position and the total of points obtained by each team at the end of the season were registered for the analysis of the association between team success and match running performance. The main findings were that high ranked teams covered the greatest total distance with ball possession, sprinting distance with ball possession, and completed the greatest number of sprinting actions with ball possession and maximal velocity. Moreover, total distance covered with possession of the ball and maximal velocity were the most important variables to predict the total of points obtained at the end of the season. Specifically, the relative contribution of total distance covered with ball possession to the total of points obtained was greater than maximal velocity. Training programs for professional soccer players should be focused on improving the sprint capacity and running with possession of the ball (e.g., transitional tasks and small-sided games). Moreover, this has implications for injury prevention, physical, psychological, and technical-tactical training since today`s soccer requires players to engage in repeated high-intensity actions, reach maximum speeds above 9 m/s, and develop technical-tactical coordination when running with the ball.